2017
DOI: 10.18805/lr.v0i0.8406
|View full text |Cite
|
Sign up to set email alerts
|

Role of Genomic tools for Mungbean [Vigna radiata (L.) Wilczek] improvement

Abstract: Molecular markers are routinely utilized worldwide in all major crops as a component of breeding. The pace of development of molecular markers, establishment of marker-trait associations for important agronomic traits and other genomic sources has been accelerated in other pulses than the mungbean. The efforts are underway to use high-throughput genotyping platforms besides developing more genomic resources. So far, progress in the use of marker-assisted selection as a part of mungbean breeding programmes has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Molecular markers are routinely utilized worldwide in all major crops as a component of breeding. The pace of development of molecular markers, establishment of marker-trait associations for important agronomic traits has been accelerated breeding in other pulses [10], but so far, progress in marker-assisted selection as a part of mungbean breeding programmes has been very limited [11].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers are routinely utilized worldwide in all major crops as a component of breeding. The pace of development of molecular markers, establishment of marker-trait associations for important agronomic traits has been accelerated breeding in other pulses [10], but so far, progress in marker-assisted selection as a part of mungbean breeding programmes has been very limited [11].…”
Section: Introductionmentioning
confidence: 99%
“…The availability of the entire genome sequence and affordable high-performance genotyping tools, such as genotyping by sequencing facilitate mapping of breeder desired traits, and marker development for breeding [21] [22]. Genome-wide association genetics is clearing the way for mapping agronomically important traits, but the low funds put into minor crops, such as mungbean, limits the population size for phenotyping and ultimately confines these efforts mainly to simple oligogenic or monogenic traits, and mapping bi-parental populations.…”
Section: Adaption Strategies and Breeding Progressmentioning
confidence: 99%
“…The progress in marker-assisted breeding has been limited for mung bean [ 6 ] though several studies have been carried out recently [ 7 ] with important agronomic traits [ 4 , 7 , 8 ]. International studies revealed that time to flowering in mung beans is influenced by genetic [ 9 ] and environmental factors [ 10 ] together with genotype-by-environment (G × E) interactions [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%